The gendered division of labour in the Corona-Crisis: a backlash? What is addressed in the discursive coalition between politics and the social sciences, and what remains concealed - Krucsay, Brita (Momentum Quarterly, 2023)
As a consequence of the lockdown measures to contain the COVID-19 Pandemic in Austria, 2020 saw the dawn of a novel public awareness regarding the family as the producer of “system-relevant services”. Social sciences and news media prominently and critically discussed the contradiction between the necessity of “privately” performed, gendered reproductive work and its simultaneous low social valuation and invisibility in broader public life. This paper traces the “career” of the sociological concept of “traditional gender roles” in Austrian public debates during the pandemic. In doing so, it reconstructs the process by which the potential field of conflict, stemming from the measures taken in response to the pandemic on the one side, and the resulting, empirically documented excessive strain for families on the other, was discursively neutralized by adapting and appropriating its critical content to suit coping strategies conducive to individualism and capitalism. Drawing from feminist economics and critique of ideology, this paper reconstructs the mode by which prevailing myths become entrenched under conditions of crises and explores the possible roles of sociological critique in this process.